2010
DOI: 10.1021/ic101679n
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Vanadium(III)-Ethylenediamine-N,N′-diacetato-N,N′-di-3-propionato Complexes. Critical Role of pπ-dπ Donation in Determining the Coordination Number

Abstract: Li[V(eddadp)]·3H(2)O (1a) and Cs[V(eddadp)]·2H(2)O (1b) were characterized by X-ray crystallography. 1a crystallizes in the monoclinic space group Cc with a = 11.467(7) Å, b = 13.398(8) Å, c = 12.529(8) Å, β = 114.85(4)°; V = 1746.7(2) Å(3), and Z = 4; 1b crystallizes in the monoclinic space group P2(1)/n with a = 10.265(5) Å, b = 11.673(6) Å, c = 15.507(8) Å, β = 104.29(2)°, V = 1800.6(2) Å(3), and Z = 4. The solution structure of 1 has been ascertained to be predominantly six-coordinated with a hexadentate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…While the broad bands at 742, 1040 nm for 1 and 742, 1100 nm for 2 are assigned to the d-d transition of the vanadium atom. 24,34 The absorption bands of the complex 2 relative to 1 appeared slightly red-shift, which may be attributed to the different ligands and coordination environment.…”
Section: Uv-vis Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…While the broad bands at 742, 1040 nm for 1 and 742, 1100 nm for 2 are assigned to the d-d transition of the vanadium atom. 24,34 The absorption bands of the complex 2 relative to 1 appeared slightly red-shift, which may be attributed to the different ligands and coordination environment.…”
Section: Uv-vis Spectramentioning
confidence: 98%
“…20 However, the studies of V(III) complexes were obviously less than that of V(IV) or V(V) complexes reported and metal centre of concerning V(III) complexes was six-coordinate mode, while studies on V(III) complexes with seven-coordinate were relatively rare. [21][22][23][24][25][26][27] Although our group has a long-standing interest in the investigation of vanadium complexes with poly(pyrazolyl)borate ligands, 28 Schiff-base ligands 29 and dicarboxylic acid ligands, 30 in order to further extend the structural variety and investigate the relationship between structure and function of the vanadium complexes, here, we firstly designed and synthesized two novel sevencoordinate vanadium(III) complexes with rigid polycarboxylate as ligands, V(dipic 2), and studied the catalytic properties in the aspect of aryl-bound bromosubstituent and oxidation of cyclohexane. It was rather surprising that high catalytic efficiency with total turnover number (TON) value of 395 was reached in the cyclohexane oxidation under mild conditions, which is much higher than the TON values (19, 167 or 308) which have been reported in previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…27 Although the V 3+ ion in 5 does not bond directly to the Se atom from the [As 2 Se 5 ] 4− anion, it adopts a distorted octahedral geometry with a low symmetry ligand field. 28 Meanwhile, the [V III (en) 3 (O)] 3+ unit is further condensed to form the dinuclear complex [V 2 (en) 6 (μ 2 -O)] 4+ cation, possibly causing a decrease in bandgap energy. Moreover, the condensation of the simple [AsSe 3 ] 3− anion might also result in the decrease of the band gap energy.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the vanadium centre in [Li][V(eddadp)] (eddadp = ethylenediamine-N,N 0 -diacetato-N,N 0 -di-3propionato) was determined to be six-coordinate in contrast to the analogous seven coordinate [V(edta)] complex. 21 An imido-bridged bimetallic vanadium complex, [(Me 2 N) 2 V(m-NAr) 2 V(NMe 2 ) 2 (NHMe 2 )] (Ar = 2,6-i Pr 2 C 6 H 3 ) was synthesised by a transamination reaction of ArNH 2 with [V(NMe 2 ) 4 ]. 22 The reversible thermochromic behaviour of [{V(OR 4 ) n ] (R = i Pr, s Bu, Np and Cy; n = 1, 2) was examined.…”
Section: Vanadiummentioning
confidence: 99%